Pengaruh Kecepatan, Kelincahan, Dan Motivasi Terhadap Kemampuan Menggiring Bola Pada Permainan Sepakbola Murid SD Inpres Bontomanai Makassar - Nurwirhanuddin; Suprianto (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2020)
The study aims at examining the speed, agility, and motivation on ball dribbling abilities in football game of students at SD Inpres Bontomanai Makassar. The populations of the study were all students class 4, 5 and 6 at SD Inpres Bontomanai. The samples were taken by purposive sampling technique. The study is descriptive research with path analysis research. Data were analyzed by employing statistics descriptive analysis and inferential analysis with SPSS 22 program. The results of the study are: (1) there is direct influence significantly of speed on motivation in football game of students at SD Inpres Bontomanai Makassar by 34%, (2) there is direct influence significantly of agility on motivation in football game of students at SD Inpres Bontomanai Makassar by 61%, (3) there is direct influence significantly of speed on ball dribbling abilities in football game of students at SD Inpres Bontomanai Makassar by 33%, (4) there is direct influence significantly of agility on ball dribbling abilities in football game of students at SD Inpres Bontomanai Makassar by 37%, (5) there is direct influence significantly of motivation on ball dribbling abilities in football game of students at SD Inpres Bontoimanai Makassar by 33%, (6) there is direct influence significantly of speed on motivation in football game of students at SD Inpres Bontomanai Makassar by 11%, and (7) there is direct influence significantly of agility on motivation in football game of students at SD Inpres Bontomanai Makassar by 20%.